THE EFFECT OF USING GOOGLE CLASROOM ON EFL LEARNERS’ MOTIVATION (مجلة ديالى للبحوث الانسانية, 2023)
ABSTRACTA classroom, in general, is an unnatural situation, thus students are in need of motivation. Many methods are being used in order to grab the attention of the students during and after class. In the literature, it is obvious that motivation increases the learning outcome of EFL students. Technology improves and advances every day in our lives, so it would only make sense if our EFL classrooms adapted themselves in a way to integrate technology in the process of teaching and learning EFL. A sample of EFL learners were chosen to participate in this quantitative type research. Later, the results of the questionnaires were analyzed via figuring out their respective Chi-square results. To be more precise and to prove this point in the University of Halabja, the questionnaire was distributed among 39 EFL students at the college of basic education, department of English language. The result supported that, indeed, using Google Classroom does increase motivation of EFL students.